Adsorption of reactive red120 using calcine and uncalcine Mg-Al-C0₃ layered double hydoxide from aqueous solution / Oumar Moechtar Mohammad Hashim - Mohammad Hashim, Oumar Moechtar (Faculty of Applied Sciences, 2009)
Using Layered Double Hydroxides (LDHs) as adsorbent for removal of Reactive red 120 and from aqueous solution at various parameters. This parameter include concentration, contact time, ph, size of particles, temperature and adsorbent dosages. The adsorption isotherms can be defined with Langmuir model instead of Freundlich model. The characterization of this Layered Double Hydroxide are determine by using several test like X-Ray Diffractometer test, the FTIR Fourier Transmitted Infrared, and SEM Scanning Electron Microscope test.